Experimental dynamometer emulation of nonlinear mechanical loads - Akpolat, ZH; Asher, GM; Clare, JC (Ieee-Inst Electrical Electronics Engineers Inc, 1999)
Industrial processes often contain nonlinear mechanical loads driven by electrical drives. Linear classical controllers, widely used in industrial drives, may not give satisfactory results for some nonlinear loads, since they are linear controllers. Adaptive, robust, and intelligent nonlinear control methods are attracting considerable attention to design a good controller for these nonlinear mechanical loads, As far as research is concerned, it is not practical to have different kinds of linear or nonlinear mechanical loads in the laboratory. The solution is to have a programmable load emulator (dynamometer) to provide realistic nonlinear loads for the experimental validation of advanced control techniques in the laboratory. This paper describes a dynamometer control strategy in which the emulation preserves the dynamic structure of a desired load model, so that the emulation can be used in closed-loop control. Experimental results of the closed-loop control of some nonlinear loads are presented. Computer simulation results are also provided for comparison purposes to show the performance of the proposed load emulation method.
1998 Industry-Applications-Society Annual Meeting -- OCT 12-16, 1998 -- ST LOUIS, MISSOURI
Keywords: drive control; programmable dynamometer